Diagnosis and treatment of portal hypertension in children (Part II: treatment) - Rafael Trinchet Soler; Yanet Hidalgo Marrero; Luis Marcano Sanz; Ramón Villamil Martínez (Medisur)
The portal hypertension is the clinical syndrome characterized by the increase of pressure in portal system. Undoubtedly the gastrointestinal bleeding due to esopagheal and gastroesophageal varices, erosive gastritis and peptic ulcers constitute the most difficult and dangerous challenge for doctors and patients. Although most patients are treated by non-surgical methods, the surgical treatment correctly realized in chosen patients according to the current protocols is the most effective method to diminish the portal pressure definitively and can be carried out in more than 88% of patients smaller than 2 years old with a near elective mortality to 0% in some countries. We presented the Second Part of Good Clinical Practices Guideline for Portal hypertension (management), approved by consensus in the 1st National Good Clinical Practices Workshop in Pediatric Surgery (Cienfuegos, Cuba, March 7 – 9, 2002).